FRACTIONATION OF SULFUR ISOTOPES DURING BACTERIAL SULFATE REDUCTION IN DEEP OCEAN SEDIMENTS AT ELEVATED TEMPERATURES - Rudnicki M.D.; Elderfield H.; Spiro B. (My University, 2001)
A numerical model of sulfate reduction and isotopic fractionation has been applied to pore fluid SO42- and δ34S data from four sites drilled during Ocean Drilling Program (ODP) Leg 168 in the Cascadia Basin at 48°N, where basement temperatures reach up to 62°C. There is a source of sulfate both at the top and the bottom of the sediment column due to the presence of basement fluid flow, which promotes bacterial sulfate reduction below the sulfate minimum zone at elevated temperatures. Pore fluid δ34S data show the highest values (135 %%) yet found in the marine environment. The bacterial sulfur isotopic fractionation factor, α, is severely underestimated if the pore fluids of anoxic marine sediments are assumed to be closed systems and Rayleigh fractionation plots yield erroneous values for α by as much as 15%% in diffusive and advective pore fluid regimes. Model results are consistent with α = 1.077 +/- 0.007 with no temperature effect over the range 1.8 to 62°C and no effect of sulfate reduction rate over the range 2 to 10 pmol cm-3 d-1. The reason for this large isotopic fractionation is unknown, but one difference with previous studies is the very low sulfate reduction rates recorded, about two orders of magnitude lower than literature values that are in the range of μmol cm-3 d-1 to tens of nmol cm-3 d-1. In general, the greatest 34S depletions are associated with the lowest sulfate reduction rates and vice versa, and it is possible that such extreme fractionation is a characteristic of open systems with low sulfate reduction rates.